Audit of pre-hysterectomy medical treatment - Chavda, Nilesh; Tailor, Shruti; Verma, Ragini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Variations in rates of hysterectomy have been observed and have been associated with women demographic characteristics such as race, socio-economic status, educational status and geographic location. However, with the advent of novel medical and conservative measures, there are doubts on justification of hysterectomy. Aims and objectives were to study prior treatment taken with respect to clinical profile in women undergoing hysterectomy in a tertiary care centre. Methods: An observational study was conducted by collecting data from medical records of 72 consenting subjects undergoing hysterectomy for benign gynaecological reasons in a tertiary care centre over a period of 12 months after ethics approval. Results: Out of 72 subjects, only 34 subjects (47.22%) had taken a prior medical treatment before undergoing hysterectomy. 100% of the subjects with endometriosis, chronic PID and DUB had taken some form of prior treatment whereas 27.5% of subjects with fibroid and 68.75% of subjects with adenomyosis had taken prior treatment. Conclusions: Our study indicates that prior medical management is not being adequately discussed and trialled among women undergoing hysterectomy. Hence, improving the counselling and understanding the women’s perspective for resistance towards medical management is an important area for research in improving quality of health care.